Analysis Of The Impact Of Community-Based Tourism Development On The Welfare Of The Batulayang Village Community Bogor - Shanty Hadiningsih; Fauziah Eddyono (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Desa Batulayang in Bogor Regency has developed as a community-based tourist village by optimizing natural, cultural, and agro-tourism potential to improve the welfare of the community. Various attractions, such as Curug Kembar, forest tourism, and traditional arts, continue to be developed through active community participation. The commitment to sustainable tourism is reflected in the certification of tourist villages as well as the development of ecotourism and agritourism, which increasingly attract the interest of tourists. This research aims to analyze the impact of community-based tourist village development on the quality of life of the community and its effect on their well-being. The measurement is based on the perceptions of the village community, with data analysis using the Partial Least Square (PLS) method based on Structural Equation Modeling (SEM). Hypothesis testing was conducted through factor analysis with a loading factor threshold >0.7. The research results indicate that the development of CBT based on economic, cultural, and environmental factors has a significant impact on the quality of life of the community, which ultimately leads to an improvement in their well-being. Keywords: Community-Based Tourism (CBT), Local Economic Impact, Community Quality of Life, Socio-Cultural Impact